“Auditoría a la gestión de inventarios y su impacto en la rentabilidad de la empresa amazoncocoa S. de la ciudad de Quinsaloma, año 2019”. - Paredes Escobar, Katty (2021)
The present investigation was carried out in the company Amazoncocoa S.A. of the city of Quinsaloma, in order to evaluate inventory management and its impact on profitability, providing a reasonable degree of security in each of the activities carried out. As well as the level of compliance with policies and regulations applied in the study area was determined. Finally, indicators of efficiency, efficacy, and effectiveness in inventory management were considered, which made it possible to permanently monitor compliance with institutional goals related to profitability. This work significantly favored the improvement of the inventory cycle process, optimizing the deficient internal inventory control that exists in the winery and the lack of monitoring of the physical inventory taking processes. For this reason, the methodology that was used was under the explanatory, descriptive and exploratory approach. Through these methods, the results of the operations carried out were analyzed and the results obtained on the management of inventories reflected notable weaknesses in their procedures, one of the main causes being the lack of a policy manual, which is why the company maintains low levels profitability. Keywords: Internal Control, Inventories - Profitability